Intense Ground-State Charge-Transfer Interactions in Low-Bandgap, Panchromatic Phthalocyanine-Tetracyanobuta-1,3-diene Conjugates - Sekita, Michael; Ballesteros, Beatriz; Diederich, Francois; Guldi, Dirk Michael; Bottari, Giovanni; Torres, Tomas (Angewandte Chemie International Edition, 2016)
A cycloaddition-retroelectrocyclization reaction between tetracyanoethylene and two zinc phthalocyanines (ZnIIPcs) bearing one or four anilino-substituted alkynes has been used to install a strong, electron-accepting tetracyanobuta-1,3-diene (TCBD) between the electron-rich ZnIIPc and aniline moieties. A combination of photophysical, electrochemical, and spectroelectrochemical investigations with the ZnIIPc-TCBD-aniline conjugates, which present panchromatic absorptions in the visible region extending all the way to the near infrared, show that the formal replacement of the triple bond by TCBD has a dramatic effect on their ground- and excited-state features. In particular, the formation of extremely intense, ground-state charge-transfer interactions between ZnIIPc and the electron-accepting TCBD were observed, something unprecedented not only in Pc chemistry but also in TCBD-based porphyrinoid systems.
CRIS-Team Scopus Importer:2023-03-07
Keywords: charge transfer; donor-acceptor systems; photophysics; phthalocyanines; tetracyanobutadienes